Web-Based Village Fund Assistance Distribution Information System Using the Quota Based Method - Damanik, Elfira Shenita; Suendri S (Politeknik Ganesha Medan, 2023)
The development of information technology has greatly influenced several aspects of human life in the implementation of daily activities. One of the benefits of the development of information technology is that it can help local governments provide information regarding the distribution of financial assistance through monitoring. Village fund assistance is one of the government programs aimed at economic recovery for people affected by the pandemic. Currently, assistance from village funds is often not supported by good governance in every village. Particularly in Tanah Merah Village, aid arrangements were still carried out by recording manually, so sometimes data input errors occurred which resulted in inaccurate data. Therefore, we need a computerized system that can overcome the limitations and problems that occur. In making this system using the Waterfall method, the stages are needs analysis, application design, system design, testing, and system maintenance. The tools used to design this system are UML (Unified Modeling Language), which consists of Use Case Diagrams, Activity Diagrams, and Class Diagrams. The results of this study are an information system for distributing village fund assistance at the Tanah Merah Village office. The application of this information system for distributing village fund assistance can help provide alternative solutions for the village government to problems in the data collection process so that the implementation process can achieve its objectives properly.